Health Responses to a Wealth Shock: Evidence from a Swedish Tax Reform - Oscar Erixson (Research Institute of Industrial Economics (IFN), 2014)
This essay contributes in two ways to the literature on the effects of economic circumstances on health. First, it deals with reverse causality and omitted variable bias by exploiting exogenous variation in inherited wealth generated by the unexpected repeal of the Swedish inheritance tax. Second, it analyzes responses in health outcomes from administrative registers. The results show that increased wealth has limited impacts on objective adult health over a period of six years. This is in line with what has been documented previously regarding subjective health outcomes. If anything, it appears as if the wealth shock resulting from the tax reform leads people to seek care for symptoms of disease, which result in that cancer is detected and possibly treated earlier. One possible explanation for this preventive response is that good health is needed for enjoying the improved consumption prospects generated by the wealth shock.
Keywords: D10; H30; I10; I12; I14; 330; Inheritances; Tax reform; Wealth shock; Objective health